(untitled) (Research, Society and Development, 2025)
This study aimed to conduct an integrative literature review to investigate the relationship between sleep bruxism (BS) and obstructive sleep apnea (AOS), based on articles published between 2014 and 2024. Sleep bruxism is an activity of the masticatory muscles during sleep, which can be phasic or tonic, while AOS is characterized by the interruption of airflow due to airway blockage. The review included studies found in databases such as PubMed and Cochrane Library, using the descriptors “sleep bruxism” and “obstructive sleep apnea”. The research revealed that AOS can increase bruxism activity, mainly due to frequente awakenings caused by apnea episodes. However, despite the association between the two disorders, the literature presents divergences regarding the real extent of this relationship. Studies indicate that individuals with severe AOS tend to have a higher prevalence of bruxism, but there is no consensus on the exact mechanisms that connect these two conditions. The study concludes that more research is needed to establish a clear and understandable link between BS and AOS, with a view to improving the diagnosis and treatment of both conditions.